Impact of Abrasion on Coastal Ecotourism Area in Medang Kampai District, Dumai City, Riau Province - Harahap, Anugrah Ramadhan; Mulyadi, Aras; Rifaldi, Rifaldi (Faculty of Fisheries and Marine, Universitas Riau, 2023)
One of the tourism areas in Dumai City is Medang Kampai District, which is a coastal area with an area of ​​373.00 km2. Coastal areas are always used for human activities, one of which is coastal ecotourism which is a coastal tourism activity developed with a conservation approach and utilizing the characteristics of coastal resources as tourist destinations. Medang Kampai District has many coastal ecotourism areas, including Pulai Humpback Beach, Pesona Alam Mundam Beach, Aulia Dumai Beach, Marina Puak Beach, Koneng Beach, Acacia Indah Guntung Beach and Legenda Beach. The method used in this study is a survey method, which was set at 5 (five) research locations, namely Pesona Alam Mundam Beach (Station I), Aulia Dumai Beach (Station II), Koneng Beach (Station III), Acacia Indah Guntung Beach (Station IV), and Legenda Beach (Station V). Based on the results of data processing using DSAS software, the results showed that the coast in the Medang Kampai sub-district was dominated by abrasion with an average abrasion rate of -2.96 m/year. The highest abrasion occurred at Acacia Indah Guntung Beach, followed by Pesona Alam Mundam Beach, Legenda Beach, Aulia Dumai Beach, and Koneng Beach. The impact on the coastal ecotourism area due to abrasion is that several facilities and infrastructure have been damaged and there has been a reduction in the area of ​​coastal ecotourism which is thought to cause a reduction in the capacity of visitors while at the same time directly impacting the economy of the local community whose livelihoods depend on coastal ecotourism.